The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.5539/gjhs.v4n6p204
|View full text |Cite
|
Sign up to set email alerts
|

Eating Behaviors of Older Adults Participating in Government-Sponsored Programs with Different Demographic Backgrounds

Abstract: The purpose of this study was to determine the food behaviors of nutritionally high-risk seniors as a function of their racial background, gender, marital status, and education level. A total of 69 seniors were identified to be at high nutritional risk using the Nutrition Screening Initiative (NSI) checklist. A supplemental questionnaire (SQ) was created to examine the risk factors in relation to the participant’s demographic background. Key results indicated that Asians practiced healthy food behaviors and wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 18 publications
2
12
0
4
Order By: Relevance
“…As a result, the Comprehensive Lifestyle Intervention or Comprehensive Cardiac Rehabilitation Program in this study significantly improved all variables in agreement with the study of Ungsinun (2011) , which found that the risk of metabolic syndrome of 3,414 people from non-government organizations (NGOs), after engaging in the Health Behavioral Modification Program (HBMP) five times in the previous 4-7 months with 3 self-behavior variables including self-efficacy, self-regulation and self-care, are significantly higher and decreased body mass index significantly ( p <.001). The similar study of Ungsinun (2012) in 4,649 people who are at risk of metabolic syndrome from 17 hospital, after engaging in the Health Behavioral Modification Program (HBMP) for 5-7 months found that the same 3 self- behavior variables increased significantly and BMI decreased significantly ( p <.005). Janssen (2012) performed meta-analysis of 23 trials involving 11,085 randomized patients to determine the efficacy of lifestyle modification programs for coronary heart disease patients developed over the last decade (1999-2009) and the results showed lifestyle modification programs positively affected risk factors and related lifestyle behaviors at post treatment (mean=10.2 months), and some of these benefits were maintained at long-term follow ups (mean=33.7 months).…”
Section: Discussionmentioning
confidence: 98%
“…As a result, the Comprehensive Lifestyle Intervention or Comprehensive Cardiac Rehabilitation Program in this study significantly improved all variables in agreement with the study of Ungsinun (2011) , which found that the risk of metabolic syndrome of 3,414 people from non-government organizations (NGOs), after engaging in the Health Behavioral Modification Program (HBMP) five times in the previous 4-7 months with 3 self-behavior variables including self-efficacy, self-regulation and self-care, are significantly higher and decreased body mass index significantly ( p <.001). The similar study of Ungsinun (2012) in 4,649 people who are at risk of metabolic syndrome from 17 hospital, after engaging in the Health Behavioral Modification Program (HBMP) for 5-7 months found that the same 3 self- behavior variables increased significantly and BMI decreased significantly ( p <.005). Janssen (2012) performed meta-analysis of 23 trials involving 11,085 randomized patients to determine the efficacy of lifestyle modification programs for coronary heart disease patients developed over the last decade (1999-2009) and the results showed lifestyle modification programs positively affected risk factors and related lifestyle behaviors at post treatment (mean=10.2 months), and some of these benefits were maintained at long-term follow ups (mean=33.7 months).…”
Section: Discussionmentioning
confidence: 98%
“…The instrument was tried out 50 students who were overweight but not participating in the study. The Cronbach's alpha coefficient of the questionnaire follows: 1) 28 items (Supitcha et al, 2012) for the self-care with the α equal to 0.81, 2) 31 items ( Intarakamhang, 2009 ; Supitcha et al, 2012) for the self-regulation which α equal to 0.81, 3) 12 items ( Intarakamhang, 2009 ; Supitcha et al, 2012) for self-efficacy with α equal to 0.89, 4) 18 items ( Intarakamhang, 2012 ) for attitude towards health behavior with α equal to 0.93, and 5) 18 items ( House & Kahn, 1985 ) social support with α equal to 0.94.…”
Section: Methodsmentioning
confidence: 99%
“…It helps achieve cooperation in the performance of the tasks and leads to the development of and changes in goals that are self-defined by the groups. The group members help to develop knowledge, skills, attitudes, and share their learning experiences helping each other in problem solving and builds confidence which carries over into daily life ( Intarakamhang & Duangchan, 2012 ). This research studies the effects of the HBMCCP program for health behavioral modification that emphasizes the self-efficacy, self-regulation, self-care behaviors and body weight of the obese students.…”
Section: Introductionmentioning
confidence: 99%
“…O envelhecimento humano relaciona-se com modificações na composição corporal deixando os idosos mais propensos à riscos nutricionais 9 . Essas alterações nas circunstâncias da vida tornam mais difíceis para os idosos manterem seus hábitos alimentares normais 10 . São escassos os estudos referente à determinação de pontos de corte de IMC para idosos, sendo assim classificações inadequadas podem estar sendo utilizadas para pacientes geriátricos 11,12 .…”
Section: Introductionunclassified